2010
DOI: 10.1007/s10902-010-9187-9
|View full text |Cite
|
Sign up to set email alerts
|

Surviving the Transformation: Social Quality in Central Asia and the Caucuses

Abstract: This paper develops a sociologically informed understanding of what influences the lives and life-choices of people living in Kazakhstan and Kyrgyzstan (Central Asian Republics) and Armenia and Georgia (the Caucasus), four of the successor states of the Soviet Union that suffered significant social and economic changes following the collapse of the Union in 1991. The focus is on the nature of these societies for their citizens; ultimately we are concerned to understand what makes a society liveable for all, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…In a Chinese context, Yuan and Golpelwar (2012) used recommendations from Abbott and Wallace for indicator variables, and analysing these variables separately, found that all four conditional factors of social quality had strong (but differing) links with subjective well-being. In an analysis of survey data from three Chinese cities, Lin (2014) also analysed social quality variables separately, but found that social inclusion was less influential than the other domains, consistent with Abbott et al’s (2010) study.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…In a Chinese context, Yuan and Golpelwar (2012) used recommendations from Abbott and Wallace for indicator variables, and analysing these variables separately, found that all four conditional factors of social quality had strong (but differing) links with subjective well-being. In an analysis of survey data from three Chinese cities, Lin (2014) also analysed social quality variables separately, but found that social inclusion was less influential than the other domains, consistent with Abbott et al’s (2010) study.…”
Section: Introductionsupporting
confidence: 69%
“…This model has been operationalised successfully in cross-national comparative research in Europe (East and West) (Abbott et al 2010; Abbott and Wallace 2012, 2014) and East Asia (Lin 2014; Yee and Chang 2011) but is only now being applied to solely British data sets. This application is timely because social quality is the only comprehensive model designed to evaluate the quality of society, as opposed to the wide variety of measures of quality of life at the individual level (Phillips 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining the factors associated with feeling lonely and its relation with health outcomes across a number of countries that differ not only culturally, ethnically, religiously, and economically, but also in terms of the way their populations have reacted to the changes that have occurred in the post-Soviet period [31], is an essential task when it comes to gaining a better understanding of the relation between loneliness and health and whether it varies between countries.…”
Section: Introductionmentioning
confidence: 99%
“…I am grateful to an anonymous reviewer for drawing attention to this connection. [28][29][30][31][32]. Eastern Europe and the Balkans experienced a similar phase of reorganization and it took years for societal expectations and lived experiences to realign, and in some cases pronounced public ambivalence, or indeed resistance, to newly predominant lifeways remains a palpable feature of these countries [33][34][35].…”
Section: Brief Insights From Recent and Ongoing Transitionsmentioning
confidence: 99%